All about learning methods: Past, Present and Future - Hafeez, Muhammad; Hasbi, Muhammad (ETDC: Indonesian Journal of Research and Educational Review, 2023)
Learning methods play a vital role in instructional pedagogy. Different learning methods are available that are being used according to the learning environment and educational levels. The objectives of this review study were to discuss the different past, current, and future learning methods. The past learning methods consisted of traditional learning methods, discussion learning methods, and module-based learning. The current learning methods consist of flipped learning methods, online learning methods, digital game-based learning methods, blended learning methods, project-based learning methods, inquiry-based learning methods, case-based learning methods, problem-based learning methods, and concept-based learning methods. The future learning methods consisted of artificial intelligence-based learning methods. All these methods have been discussed in this review article.